2021
DOI: 10.1186/s13195-021-00808-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel age-informed approach for genetic association analysis in Alzheimer’s disease

Abstract: Background Many Alzheimer’s disease (AD) genetic association studies disregard age or incorrectly account for it, hampering variant discovery. Methods Using simulated data, we compared the statistical power of several models: logistic regression on AD diagnosis adjusted and not adjusted for age; linear regression on a score integrating case-control status and age; and multivariate Cox regression on age-at-onset. We applied these models to real exom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 63 publications
(114 reference statements)
3
28
0
Order By: Relevance
“…In the ADSP WES data, TREM2 and ABCA7-wellestablished AD risk genes 2,6 -were observed with variants, respectively, at genome-wide and suggestive significance, consistent with observations for similar models in prior studies on the prior ADSP WES discovery phase data. 7,15 Despite observing only 4 variants in ADSP WES that passed suggestive significance in model 2, our findings were overall highly consistent with prior work. 15 We also observed that certain variants identified previously were not present in our current summary statistics (eTable 10, links.lww.com/NXG/A536), reflecting differences in joint calling, QC, and the fact that currently only biallelic data were available for the new ADSP WES data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the ADSP WES data, TREM2 and ABCA7-wellestablished AD risk genes 2,6 -were observed with variants, respectively, at genome-wide and suggestive significance, consistent with observations for similar models in prior studies on the prior ADSP WES discovery phase data. 7,15 Despite observing only 4 variants in ADSP WES that passed suggestive significance in model 2, our findings were overall highly consistent with prior work. 15 We also observed that certain variants identified previously were not present in our current summary statistics (eTable 10, links.lww.com/NXG/A536), reflecting differences in joint calling, QC, and the fact that currently only biallelic data were available for the new ADSP WES data.…”
Section: Discussionsupporting
confidence: 90%
“…2 In response to this observation, there has been a shift to start using exome sequencing (ES) or genome sequencing (GS) to help capture rare and/or coding variants that contribute to AD risk, which has led to several recent initial successes. [7][8][9][10][11][12][13][14][15] In the United States, the Alzheimer Disease Sequencing Project (ADSP) has taken a leading role in the sequencing of AD-related samples at scale, with resultant data being made publicly available to researchers to generate new insights into the genetic etiology of AD. The ADSP has pursued both "whole" ES (WES) and "whole" GS (WGS) approaches (although it should be noted that these for now do not actually provide whole coverage due to technical limitations), where most recently, the focus is increasingly on GS.…”
mentioning
confidence: 99%
“…Some weaker correlations are observed for studies that use different phenotype definitions. For example, Huang et al (2017) is weakly correlated with other major AD GWAS because the authors performed a time-to-event survival analysis; the correlation between Le Guen et al (2021) and Bis et al (2019) is weaker than that between our in-house ADSP WES analysis and Bis et al (2019), because Le Guen et al (2021) used a new age-informed AD phenotype instead of clinical AD.…”
Section: Supplementary Materialsmentioning
confidence: 67%
“…In-house genome-wide associations study of 15,209 cases and 14,452 controls aggregating 27 cohorts across 39 SNP array data sets, imputed using the TOPMed reference panels 47 ; 6-7. Two whole-exome sequencing analyses of data from The Alzheimer’s Disease Sequencing Project (ADSP) by Bis et al 2019 48 (5740 cases, 5096 controls), and Le Guen et al 2021 49 (6008 cases, 5119 controls); 8. In-house whole-exome sequencing analysis of ADSP (6155 cases, 5418 controls); 9.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the association of individual genetic variants with AD in all qualifying participants (N=9,746), we performed logistic regression in PLINK (v1.9) using an additive model while adjusting for sex, APOE ε2 and ε4 dose, sequencing centers and the first three PCs accounting for population substructure. Since the ADSP cohort was enriched for older controls (Additional File 1), we did not include age as a covariate in the regression model as correcting for age when individuals with AD are younger than controls leads to the model incorrectly inferring the age effect on AD risk, resulting in loss of statistical power [43]. Variants in the APOE region [44] (chr19: 44,495,939-45,296,742; GRCh38) were excluded from this analysis.…”
Section: Genome-wide Association Study (Gwas)mentioning
confidence: 99%